Asymmetric Isothiourea‐Catalysed Formal [3+2] Cycloadditions of Ammonium Enolates with Oxaziridines. Issue 29 (12th June 2015) - Smith, Siobhan R.; Fallan, Charlene; Taylor, James E.; McLennan, Ross; Daniels, David S. B.; Morrill, Louis C.; Slawin, Alexandra M. Z.; Smith, Andrew D.
Abstract A highly enantioselective Lewis base‐catalysed formal [3+2] cycloaddition of ammonium enolates and oxaziridines to give stereodefined oxazolidin‐4‐ones in high yield is described. Employing an enantioenriched oxaziridine in this process leads to a matched/mis‐matched effect with the isothiourea catalyst and allowed the synthesis of either syn‐ or anti‐stereodefined oxazolidin‐4‐ones in high d.r., yield and ee. Additionally, the oxazolidin‐4‐one products have been derivatised to afford functionalised enantioenriched building blocks.